TINJAUAN KRIMINOLOGIS TERHADAP KEJAHATAN PERTAMBANGAN TANPA IZINDI KABUPATEN LUMAJANG - Totok Sugiarto , Budi Hariyanto (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2018)
This study was conducted with the aim to identify criminological review of illegal mining crimes in Lumajang District. This study used a normative juridical approach. Data were collected by interview and documentation and analyzed by qualitative descriptive technique. The results of this study found that unlicensed mining is caused by social factors, legal factors and economic factors. Social factors include (1) the existence of traditional miners by local communities that have taken place for generations, (2) a less harmonious relationship between official and licensed mining with the local community, (3) misinterpretation of reforms defined as unlimited freedom. Legal factors include (1) public ignorance of the prevailing laws and regulations in the mining sector, (2) weakness of mining laws and regulations, which among others are reflected in the impartiality of the public interest and the absence of reprimands to the official / licensed mining Which does not take advantage of its business area (sleeping land), (3) weaknesses in law enforcement and supervision. Economic factors include (1) limited employment and employment opportunities that are appropriate to the level of skills / skills of the lower society, (2) poverty in many ways, poor economically, knowledge and skill, (3) the existence of third parties who use poverty for certain purposes , Ie funders (cukong), backing (officer apparatus) and NGOs, (4) prolonged economic crisis that gave rise to unemployment, especially from the lower community. The discovery of new reserves by authorized / licensed mining companies.